Green Electrospinning - Crespy, Daniel; Demir, Mustafa M.; Horzum, Nesrin; Muñoz-Espí, Rafael (De Gruyter, 2019)
The last two decades have seen electrospinning of nanofibers performed mainly from solutions of toxic organic solvents. The increase in demand for scaling up electrospinning in recent years therefore requires an environmentally friendly process free of organic solvents. This book addresses techniques for clean and safe electrospinning in the fabrication of green nanofibers and their potential applications.- Resumé vydavatel
Keywords: elektrostatické zvlákňování; environmentálně vhodné technologie; biopolymery; nanovlákna; electrospinning; green technology; biopolymers; nanofibers; elektronické knihy; kolektivní monografie; electronic books; collective monographs